Physicochemical Properties of Bird’s Nest Orange Drink Treated Using Different Retort Times and Cooling Processes - Maimanah Faizah, Idris; Phang, Lok Ying; Rozzamri, Ashari (Malaysian Applied Biology, 2025)
Bird’s nest drinks are widely recognised as a healthy beverage option. Introducing a bird’s nest orange drink represents a promising advancement in food technology, anticipated to offer enhanced health benefits. This study focuses on retort sterilisation, a crucial method for ensuring food safety and quality. However, prolonged retort processing can negatively impact beverage characteristics. This study investigated the effects of varying retort times (3, 5, and 7 minutes at 121°C) and cooling methods (room temperature and ice bath) on bird’s nest orange drink properties. The main goal was to find the best processing conditions to maintain product quality. Results showed that retort time significantly (p < 0.05) impacted most physical and chemical traits, including moisture, protein, fat, pH, total soluble solids, viscosity, and colour (L* values). Longer retort times decreased (p < 0.05) these properties, while ash and carbohydrate content, and redness/yellowness (a* and b* values), increased (p < 0.05). Cooling methods had less impact, mainly affecting (p < 0.05) viscosity and lightness, with ice water cooling performing slightly better. Crucially, the drink’s ability to scavenge free radicals notably (p < 0.05) declined with longer retort times, regardless of the cooling method. This shows that heat treatment degrades the antioxidants. The findings highlight a trade-off between ensuring microbial safety and preserving the drink’s nutritional and sensory quality, emphasising the importance of optimising thermal processing parameters for bird’s nest orange drinks.